Evaluation Of The Auto Surfacing Methods To Create A Surface Body Of The Mandible Model - K.Shanmugasundaram; R.Niranjan; P.J.Aruloli (Revista Electronica de Veterinaria, 2024)
It’s not easy to design an anatomical structure for a surgical treatment. This is particularly true for the craniofacial region, which is made up of bone tissues with extremely intricate geometries. To make the most of the tools that are currently accessible in connected procedures with the building of the craniofacial areas, CAD modelers need to possess the necessary knowledge and abilities in both technological sciences and medical. The four patients treated at the Department of Maxillofacial Surgery form the basis of the early investigations that are being presented. Using the ITK SNAP program, the mandible model’s segmentation was completed. Two distinct approaches—organic and mechanical—were used in the Auto Surfacing module of the Geomagic software to generate surface body models. Next, evaluate the two approaches’ accuracy in creating a CAD model of the mandible using the Focus Inspection and GOM Inspect tools based on a triangle mesh structure.